2010
DOI: 10.1136/jcp.2009.069625
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous breast cancer and lymphoma: a case series and a review of the literature

Abstract: Four patients with synchronous breast cancer and lymphoma are described. In all cases, the lymphoma was an unexpected finding in the histopathology of the axillary lymph-node dissection. The diagnosis of synchronous malignancies poses challenges for both the diagnosing pathologist and the treating clinician.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 9 publications
(3 reference statements)
0
28
0
2
Order By: Relevance
“…Synchronous or metachronous presentations of BC and FL are rare, and to the best of our knowledge, only six cases have previously been reported in the literature (10–14); the present study is the seventh case. Profiles of the seven cases are summarized in Table I.…”
Section: Discussionmentioning
confidence: 68%
“…Synchronous or metachronous presentations of BC and FL are rare, and to the best of our knowledge, only six cases have previously been reported in the literature (10–14); the present study is the seventh case. Profiles of the seven cases are summarized in Table I.…”
Section: Discussionmentioning
confidence: 68%
“…Patients with lymphoma are known to be chronically immunosuppressed, which may predispose to the development of a second malignancy [10]. It has also been suggested that the antigenic stimulation from an as yet undefined breast carcinoma antigen may drive the development of a mucosa-associated lymphoid tissue (MALT) lymphoma, analogous to the effect of chronic Helicobacter pylori infection on the pathogenesis of gastric MALT lymphomas [11].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of second primary neoplasms in patients with history of malignant tumors has been well documented [2]; however, the synchronous presentation of 2 malignancies is an extremely rare event that involves approximately 0.8% of these patients [3]. …”
Section: Discussionmentioning
confidence: 99%